Time to progression predicts outcome of patients with multiple myeloma that can be influenced by autologous hematopoietic stem cell transplantation - Yanhua Yue; Yingjie Miao; Yifang Zhou; Yangling Shen; Luo Lu; Fei Wang; Yang Cao; Bai He; Weiying Gu (Hematology)
Objectives Currently, there is limited understanding regarding the prognostic significance of time to progression (TTP) after first remission in multiple myeloma (MM).Methods We conducted a retrospective analysis of clinical data from 209 patients with MM. These patients were categorized into ≤ 6 months, ≤ 12 months, ≤ 24 months, > 24 months, 6–12 months, and 12–24 months subgroups based on TTP.Results Patients in ≤ 12 months group exhibited shorter median overall survival (OS) and OS-1 compared to those in ≤ 24 months group (61.73 vs 96.10 months, P = 0.02; 54.00 vs 74.17 months, P = 0.048). ≤ 6 months group exhibited shorter median OS and OS-1 compared to 6–12 months group (33.63 vs 79.60 months, P = 0.022; 19.93 vs 65.17 months, P = 0.015). Patients in 6–12 months group had shorter median OS and OS-1 compared to those in 12–24 months group (79.60 vs 100.43 months, P < 0.001; 65.17 vs 77.17 months, P = 0.012).No significant difference in OS was observed between patients in 12–24 months and > 24 months groups. For patients who experienced progression within 12 or 24 months after remission, undergoing autologous hematopoietic stem cell transplantation (ASCT) after progression conferred a median OS and OS-2 advantage over receiving post-progression chemotherapy. Multivariable analysis confirmed that TTP was an independent predictor for OS in patients with MM.Conclusion Patients with MM who experience earlier disease progression within 12 months after remission have a worse prognosis, and post-progression ASCT can improve their survival outcomes.